PENGARUH MANAJEMEN LABA TERHADAP KINERJA SAHAM JANGKA PANJANG PERUSAHAAN YANG MELAKUKAN SEASONED EQUITY OFFERING - Pratama, Andika; Suaryana, I G.N. Agung (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This study aims to determine the policy of discretionary accrual of earnings management through its influence on the company's stock performance after implementing SEO. This study used 32 companies doing SEO and listed on the Indonesia Stock Exchange. Discretionary accrual by Modified Jones Model are showing  that there are discretionary accruals before dilaksanaknnya SEO shows the average value of positives which means companies tend to raise the earnings management practices earnings. This study founded that earnings management is proxied by discretionary accruals one year before SEO no significant effect on the performance of the company's shares three years after the offering of additional shares. The management do earning management efficient where the management company wants to give a good signal to investors to demonstrate the company had a good performance. In addition, investors increasingly intelligent assess the company's financial statements.
Keywords: Earnings Management, Stock Performance, Seasoned Equity Offering